An enigmatic multituberculate mammal from the Early Cretaceous of Siberia, Russia. Issue 2 (4th March 2017) - Averianov, Alexander; Lopatin, Alexey; Skutschas, Pavel; Ivantsov, Stepan; Boitsova, Elizaveta; Kuzmin, Ivan
ABSTRACT: Baidabatyr clivosus, gen. et sp. nov. (Multituberculata incertae sedis ), is described on the basis of an ultimate upper premolar (P5) from the Lower Cretaceous Ilek Formation at Bol'shoi Kemchug 3 locality in Krasnoyarsk Territory, Russia. The new taxon differs from all known multituberculates by the cusp formula of the ultimate upper premolar (4:5:5), cusps well separated by valleys of flat crown surface, and three roots. It shares with a few non-cimolodontan multituberculates such rare characters of the ultimate upper premolar as elongated crown with length to width ratio of 2.0 and smooth enamel. Baidabatyr, gen. nov., is plesiomorphically similar to Paulchoffatiidae in having a horizontal profile of the ultimate upper premolar in lateral view. It likely represents a late survival of the Jurassic paulchoffatiid radiation of multitituberculates. Baidabatyr, gen. nov., is another relict taxon in the Early Cretaceous mammal fauna of the Ilek Formation, otherwise dominated by docodontans, eutriconodontans, and symmetrodontans. http://zoobank.org/urn:lsid:zoobank.org:pub:AD0FE7FA-8F78-4DFF-88DD-6F56545C6576 Citation for this article: Averianov, A., A. Lopatin, P. Skutschas, S. Ivantsov, E. Boitsova, and I. Kuzmin. 2017. An enigmatic multituberculate mammal from the Early Cretaceous of Siberia, Russia. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1293070.